782 Evaluation of Ketamine Sedation as An Alternative to General Anaesthetic for The Management of Paediatric Soft Tissue Facial Injuries During the Covid-19 Pandemic. (12th October 2021) - Nijamudeen, A; Cole-Healy, Z; Clark, Stuart
Abstract: Introduction: Standard surgical practice of paediatric soft tissue facial injuries requires general anaesthetic (GA) if treatment with local anaesthetic is not tolerated. However, the Covid-19 pandemic has increased the risk of hospital admission for GA to patients and pre-operative Covid-19 testing can delay surgical treatment. In response, a service was established to facilitate short surgical procedures by the Oral and Maxillofacial surgical (OMFS) team with ketamine sedation (KS) at a tertiary level paediatric emergency department. Evaluation of this service demonstrates that KS is a suitable alternative to GA with reduced waiting times, low complications and equivalent surgical outcomes. Method: 20 patients treated under KS from May- September 2020 were identified and compared to a control group of 20 patients treated under GA during the same time period. Data including patient demographics, surgical treatment and the KS/GA procedure was collected from the medical records and was analysed using Microsoft excel. Results: The KS patients had shorter waits for treatment with 85% of patients waiting 1 day or less, compared with 55% for the GA group. Using the local KS protocol 1 or 2 doses of ketamine was sufficient in 79% of cases and adverse effects were minimal with 21% of KS patients suffering mild nausea and vomiting. Conclusions: KS is an acceptable alternative to GA for the management of paediatric soft tissue injuries. KS reduces inpatient admission for GA which is of increased importance during the Covid-19 pandemic. Other OMFS units would benefit from access to a similar service.